Towards understanding the multifaceted role of SUMOylation in plant growth and development. Issue 1 (18th September 2020) - Srivastava, Moumita; Sadanandom, Ari; Srivastava, Anjil Kumar
Abstract : Post‐translational modifications (PTMs) play a critical role in regulating plant growth and development through the modulation of protein functionality and its interaction with its partners. Analysis of the functional implication of PTMs on plant cellular signalling presents grand challenges in understanding their significance. Proteins decorated or modified with another chemical group or polypeptide play a significant role in regulating physiological processes as compared with non‐decorated or non‐modified proteins. In the past decade, SUMOylation has been emerging as a potent PTM influencing the adaptability of plants to growth, in response to various environmental cues. Deciphering the SUMO‐mediated regulation of plant stress responses and its consequences is required to understand the mechanism underneath. Here, we will discuss the recent advances in the role and significance of SUMOylation in plant growth, development and stress response.